2016
DOI: 10.1016/j.foodcont.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pomegranate powder on the heat inactivation of Escherichia coli O104:H4 in ground chicken

Abstract: Health concerns have led to a search for natural plant-based antimicrobials. Ellagic acid has been shown to have antimicrobial activity against foodborne pathogens. The objective of this study was to assess the effect of a high-ellagic acid commercial pomegranate on the heat resistance of Escherichia coli O104:H4 in ground chicken. A full 2 4 factorial design was used, consisting of temperature treatment with four levels (55.0, 57.5, 60.0, and 62.5 C) and pomegranate with four levels (0.0, 1.0, 2.0, and 3.0 wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Furthermore, the addition of pomegranate peel extended shelf-life of chicken burger to 8 and 10 days, respectively compare with 6 days for the control sample. These data confirmed by those reported with Endo et al, 2010, Hayrapetyan et al, 2012, Quattrucci et al, 2013, Finegold et al, 2014, Molva and Baysal, 2015, Juneja et al, 2016, who reported that pomegranate peel proved its effectiveness against many fungi and bacteria such as Candida albicans, Listeria monocytogenes, Pseudomonas syringaepv. Tomato, Clostridium difficile and Alicyclobacillusacidoterrestris, respectively.…”
Section: Microbial Evaluationsupporting
confidence: 89%
“…Furthermore, the addition of pomegranate peel extended shelf-life of chicken burger to 8 and 10 days, respectively compare with 6 days for the control sample. These data confirmed by those reported with Endo et al, 2010, Hayrapetyan et al, 2012, Quattrucci et al, 2013, Finegold et al, 2014, Molva and Baysal, 2015, Juneja et al, 2016, who reported that pomegranate peel proved its effectiveness against many fungi and bacteria such as Candida albicans, Listeria monocytogenes, Pseudomonas syringaepv. Tomato, Clostridium difficile and Alicyclobacillusacidoterrestris, respectively.…”
Section: Microbial Evaluationsupporting
confidence: 89%
“…peel powder meatballs ↑antioxidant activity; ↓lipid and protein oxidation; ↑microbial quality [113] peel powder beef sausage quality criteria improvement; improvement of cooking characteristics [114] juice powder raw ground chicken ↓heat resistance of E. coli [115] peel extract pacific white shrimp ↓lipid oxidation; ↓melanosis; ↓microbial growth [116] extract fish patties ↑shelf-life [117] extract pork sausage controlling microbial growth and oxidation; ↑shelf-life [118] Table 9. Recent studies on the effect of the addition of pomegranate derivatives to cereal and nut products.…”
Section: Product Effect Referencesmentioning
confidence: 99%
“…In addition, improvements of cooking characteristics, e.g., cooking loss, cooking yield, change in diameter, and change in length, were also reported. A high-ellagic acid commercial pomegranate powder has also been used to reduce the heat resistance of Escherichia coli O104:H4 in ground chicken [115]. Indeed, the time to reach a 5.0 log reduction reached a minimum at a pomegranate powder concentration of 1%, producing a 50% decrease in lethality time in comparison to that without added pomegranate powder.…”
Section: Meat and Fish Productsmentioning
confidence: 99%
“…The addition of the pomegranate peel extract to the meat products enhanced their shelf life by 2–3 weeks during chilled storage. The shelf life of meat containing pomegranate peel extracts has been studied by several authors [ 22 , 30 , 31 , 32 , 33 ]. The fruit peel has high antioxidant and antimicrobial activities and may be used as an excellent natural additive for food preservation and for quality enhancement.…”
Section: Introductionmentioning
confidence: 99%